Two-Spirit Identities in Canada: Mapping Sovereign Erotic in Joshua Whitehead’s Jonny Appleseed - Siepak, Julia (Studia Anglica Posnaniensia, 2020)
In colonial times, mapping the New World functioned as an inherent mechanism of exerting colonial domination over Indigenous lands, enacting settler presence on these territories. While the colonial cartographies projected ownership, the non-normative mappings emerging from Aboriginal writing provide an alternative to settler Canadian geography. This article focuses on the imaginative geographies depicted in Joshua Whitehead’s Jonny Appleseed (2018), which recounts the story of a young Two-Spirit man who searches for his identity in-between the reserve and the city. The objective of the analysis is to tie the representation of the contemporary queer Indigenous condition with the alternative mappings emerging from Whitehead’s novel. In order to address the contemporary Two-Spirit condition in Canada, the article applies current theories proposed by the field of queer Indigenous studies, including the concept of sovereign erotic, which further allows the presentation of the potential of Two-Spirit bodies to transgress colonial cartographies.